(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study was intended to establish the business studies teachers’ perception of the extent in which principals in Anambra State secondary schools adopt three administrative styles in their schools. Three research questions and four null hypotheses guided the study. Descriptive survey design was adopted and a population of 295 business studies teachers was used for the study. A 40-item validated questionnaire, structured on a 5-point response options with 0.96 reliability coefficient was used for data collection. Data were analyzed with the arithmetic mean, standard deviation andz-test at 0.05 level of significance. Findings revealed that secondary school principals in the area of study adopt the democratic administrative style to a high extent and adopt autocratic and laissez-faire administrative styles to a low extent. Experience did not significantly affect respondents’ opinions but gender and school location did. Based on the findings, it was concluded that secondary school teachers in Anambra State Nigeria should be well equipped on infrastructural facilities in order to perform better in decision making. It was recommended, among others, that the principals should continue to adopt democratic administrative style and also encourage their counterparts in other states to emulate them in order to enhance teacher performance.